Honesty and Motivational Character Analysis of Science Learning Achievement - Harlinda Syofyan; Ratih Ratih (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to ascertain the effect of student motivation and honesty on science learning achievement.This study used quantitative in nature and employs a survey method.Three variables will be analyzed in this study: honesty, motivation, and science learning achievement. The subject in this researxh is 53 undergraduated students. Respondents completed questionnaires distributed by the researchers. After collecting data from respondents, the data must be tested. At the time of learning, the most critical characteristic that students must instill in each individual is the character of honesty and student motivation to participate in ongoing learning. This is done so that when students are actively engaged in learning, they can be completely honest in their actions and demonstrate a strong desire to learn. As a result, if it is instilled in students, it will affect their learning achievement. The findings of this study indicate that there is a significant effect of both honesty and motivation on student science learning achievement